Plant defence genes expressed in tobacco and yeast - Becker, John van Wyk (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Viticulture and Oenology. Wine Biotechnology))--University of Stellenbosch, 2002.